Alterações hematológicas associadas ao hifema em cães - Prado, Getúlio Makowski de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
Hyphema is an intraocular hemorrhage that can result from many ocular and/or systemic disorders. It is an important clinical sign, since it may appear in the initial stages of some diseases or haematological disorders, acting as an initial marker for early diagnosis. The hematologic disturbances that predispose animals to present hyphema are: Thrombocytopenia, von Willebrand Disease, Scott Syndrome, Disseminated Intravascular Coagulation and Hyperviscosity Syndrome due to Multiple Myeloma. Each of the differential diagnoses due to hematological changes from the appearance of hyphema in dogs shows clinical relevance and particular ocular signs

Hifema é uma hemorragia intra-ocular que pode resultar de muitas alterações oculares e/ou distúrbios sistêmicos. É um importante sinal clínico, pois pode aparecer nos estádios iniciais de algumas enfermidades ou alterações hematológicas, servindo como um marcador inicial para um diagnóstico precoce. Os distúrbios hematológicos que predispõem os animais a manifestarem o hifema são: Trombocitopenia, Doença de von Willebrand, Síndrome de Scott, Coagulação Intravascular Disseminada e Síndrome da Hiperviscosidade Sanguínea por Mieloma Múltiplo. Cada um dos diagnósticos diferenciais causados por alterações hematológicas a partir do aparecimento de hifema em cães apresenta relevância clínica e manifestações oculares próprias
Keywords: Hematologia veterinaria; Cão - Doenças